Synthesis, Characterization, and In Vivo Cytokinome Profile of IL-12-Loaded PLGA Nanospheres - Ryan A. Lacinski; Justin E. Markel; Jabeen Noore; Hillary G. Pratt; Brock A. Lindsey (Journal of Immunology Research)
We report the successful encapsulation and elution of recombinant murine IL-12 (rmIL-12) from poly(lactide-co-glycolic) acid (PLGA) nanospheres (IL-12-NS) synthesized using the double emulsion/solvent evaporation (DESE) technique with microsphere depletion through ultracentrifugation. Images obtained with scanning electron microscopy (SEM) showcased a characteristic spherical shape with a mean particle diameter of 138.1±10.8 nm and zeta potential of −15.1±1.249 mV. These values suggest minimal flocculation when in solution, which was reflected in an in vivo biodistribution study that reported no observed morbidity/mortality. Encapsulation efficiency (EE) was determined to be 0.101±0.009% with average particle concentration obtained per batch of 1.66×109±4.45×108 particles/mL. Disparate zeta (ζ) potentials obtained from both protein-loaded and protein-unloaded batches suggested surface adsorption of protein, and confocal microscopy of BSA-FITC-loaded nanospheres confirmed the presence of protein within the polymeric shell. Furthermore, elution of rmIL-12 from IL-12-NS at a concentration of 500 million particles/mL was characterized using enzyme-linked immunosorbent assay (ELISA). When IL-12-NS was administered in vivo to female BALB/c mice through retroorbital injection, IL-12-NS produced a favorable systemic cytokine profile for tumoricidal activity within the peripheral blood. Whereas IFN-γ nadir occurred at 72 hours, levels recovered quickly and displayed positive correlations postburst out to 25 days postinjection. IL-12-NS administration induced proinflammatory changes while prompting minimal counterregulatory increases in anti-inflammatory IL-10 and IL-4 cytokine levels. Further, while IL-6 levels increased to 30 folds of the baseline during the burst phase, they normalized by 72 hours and trended negatively throughout the sill phase. Similar trends were observed with IL-1β and CXCL-1, suggesting a decreased likelihood of progression to a systemic inflammatory response syndrome-like state. As IL-12-NS delivers logarithmically lower amounts of IL-12 than previously administered during human clinical trials, our data reflect the importance of IL-12-NS which safely create a systemic immunostimulatory environment.